Assessment knowledge, attitude, and willingness to care for patients with HIV/AIDS among midwifery students of selected universities in Iran in 2020 - Fatemeh Mokhtari; Bahareh Kamranpour; Maryam Shakiba; Marjan Akhavanamjadi; Marjan Goli; Masoumeh Pourmohsen (Wolters Kluwer Medknow Publications, 2023)
Background: Stigmatization and discrimination by health workers, particularly midwives are obstacles to the achievement of universal access to Human Immunodeficiency Virus (HIV) prevention, treatment, and care programs. Therefore, it is necessary to evaluate midwifery students' knowledge and attitude regarding Acquired Immune Deficiency Syndrome (AIDS) and HIV, and their willingness to care for patients with AIDS and HIV before they enter the field of health and medical activities. Thus, the aim of this study was to investigate the level of knowledge and attitude in this regard, and willingness to care for patients with AIDS and HIV among midwifery students of selected universities in Iran in 2020. Materials and Methods: A descriptive-analytical, cross-sectional study was performed on 618 midwifery students in Iran in 2019-2020. Data were collected using a five-part questionnaire: a demographic characteristics form, an academic profile form, the HIV Knowledge Questionnaire (HIV-KQ), the AIDS Attitude Scale (AAS), and the Jordan Standard Questionnaire. Data analysis was performed through descriptive and inferential statistical methods. p value of ≤ 0.05 was considered significant. Results: The mean (SD) age of the subjects was 23.10 (5.63) years. The mean (SD) of knowledge, attitude, and willingness scores were 26.93 (6.64), 80.45 (9.27), and 29.55 (9.10), respectively. Single individuals had higher attitude scores. Conclusions: Iranian midwifery students had the desired level of knowledge, although the mean score was not much higher than the threshold. The level of the midwifery students' attitude was appropriate and more than that, but none of them had a 100% positive attitude. They had a moderate or neutral willingness to provide services to and care for patients with AIDS.